Water quality hazard assessment for hand dug wells in Rafin Zurfi, Bauchi State, Nigeria - Jagaba A.H.; Kutty S.R.M.; Hayder G.; Baloo L.; Abubakar S.; Ghaleb A.A.S.; Lawal I.M.; Noor A.; Umaru I.; Almahbashi N.M.Y. (Ain Shams University, 2023)
Disease control; Geographic information systems; Hazards; Health risks; Heavy metals; Information systems; Information use; Risk analysis; Risk assessment; Water quality; Analytical results; Dug well; Hazard indices; Mitigation measures; Rafin Zurfi area; Spatial variations; Target hazard quotients; Water quality indexes; Quality control